MEDIA SOSIAL BERDAMPAK PADA EKSPRESI KEBAHASAAN MASYARAKAT (TANGGAPAN MASYARAKAT MELAYU TERHADAP PERNYATAAN EFENDI SIMBOLON DI MEDIA SOSIAL) - Ida Herawati (tuahtalino, 2017)
Language as a tool to express self-expression used to express everything that is implied in the thoughts and feelings of native speakers. Language development has spawned various branches of language use; one of which is the style language or figure of speech. Style language is a unique character of a language, because it can build up and develop the imagination that exceeds the true meaning of a word by comparing,  contrasts and even repeat the word. Sarcasm is one style that is generally known by the public as a way of insinuating language, either explicitly or implicitly, orally or in writing, has been a part of human social life. As now most people often use the language style of sarcasm in his daily interactions so many create a new understanding of the style of language as part of the vast rich language.